Development of High‐Voltage Aqueous Electrochemical Energy Storage Devices. Issue 16 (10th July 2017) - Yu, Jia; Mu, Chao; Qin, Xinyu; Shen, Chao; Yan, Bingyi; Xue, Huaiguo; Pang, Huan
Abstract : High voltage aqueous electrochemical energy storage devices have gained significant attention recently due to their high safety, low cost, and environmental friendliness. Through the addition of a solid‐electrolyte interphase, usage of a concentrated electrolyte or adjustment of the pH of their electrolytes, it is hopeful to endow these aqueous energy‐storage devices with a broadened voltage. Among all of them, aqueous lithium‐ion batteries have a longer lifespan and a promising future in energy storage systems. Herein, aqueous batteries will be introduced by demonstrating their voltage improvement approaches and progress is focused. Abstract : Development of high‐voltage aqueous electrochemical energy storage devices . High‐voltage aqueous energy‐storage devices are more environmental friendly and cost‐effective. They can be applied in portal energy storage devices as well as large‐scale ones.